Perbandingan Strategi Pembelajaran Gallery Session dan Ekspositori pada Pembelajaran Pendidikan Agama Islam - Sri Juwita; Safwannur Safwannur; Hasbiyallah Hasbiyallah (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
This paper compares gallery sessions and expository learning strategies for Islamic Religious Education (PAI) learning at Ashfiya Elementary School (SD) Bandung. The method used in this study is a quasi-experiment with pretest post-test control group design. Sampling was conducted incidentally to determine the experimental and control classes. The study's results showed that the difference in the mean scores before and after the gallery session strategy in the experimental class was significant, 31.905, compared to the control class, which applied the expository strategy with a score of 22.27. The average value obtained after treatment in the experimental class was 85.25, and the control class was 75.50. The hypothesis test results show a difference in average values with a significant gain of 0.00. The gain value in the class that uses the gallery session strategy is 51.6, so it is in the medium category. While the class that uses the lecture strategy gets a gain value of 25.2, so it is in a low category. That proves that there are differences in learning outcomes with the application of the gallery session strategy compared to the expository strategy.